2010
DOI: 10.1634/theoncologist.2009-0190
|View full text |Cite
|
Sign up to set email alerts
|

Standard and Emerging Therapies for Metastatic Differentiated Thyroid Cancer

Abstract: After completing this course, the reader will be able to:1. Describe the role and limitations of traditional treatments for metastatic differentiated thyroid cancer.2. Discuss the molecular basis of and clinical evidence for novel and emerging treatments for metastatic differentiated thyroid cancer.3. Identify suitable candidates for clinical trials among your patients with radioactive iodine refractory, metastatic differentiated thyroid cancer and enroll them.This article is available for continuing medical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 117 publications
0
47
0
5
Order By: Relevance
“…Отдаленные метастазы при первичной диагностике обнаруживают менее чем в 5 % случаев. Однако рецидив заболевания возникает у 10-15 % пациентов, из них у 66 % -в первые 10 лет после первичной терапии [1]. Метастатический ДРЩЖ, который становится неопе-рабельным или резистентным к терапии РАЙ, характе-ризуется низкими показателями выживаемости.…”
Section: None Of the Variants Of Therapy Currently Available For Patiunclassified
“…Отдаленные метастазы при первичной диагностике обнаруживают менее чем в 5 % случаев. Однако рецидив заболевания возникает у 10-15 % пациентов, из них у 66 % -в первые 10 лет после первичной терапии [1]. Метастатический ДРЩЖ, который становится неопе-рабельным или резистентным к терапии РАЙ, характе-ризуется низкими показателями выживаемости.…”
Section: None Of the Variants Of Therapy Currently Available For Patiunclassified
“…Most carcinomas derived from the follicular epithelium of the thyroid gland are well differentiated ([90 %) and wellbehaved, with a 10-year disease-specific survival of 85-92 % [1,2]. These indolent cancers are localized to the thyroid gland, do not recur or metastasize beyond local lymph nodes, and are thus easily curable with hemi-or total thyroidectomy, with possible local nodal dissection and/or radioactive iodine ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Distant metastasis develops in only 1-15 % of thyroid carcinomas, but when it occurs, it decreases the 10-year survival to 10-40 % [2,3]. The latest data from Cancer Care Ontario has shown that distant metastasis occurs in \1 % of thyroid cancer patients [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Место совмещенной позитронно-эмиссионной и компьютерной томографии с 18-фтордезоксиглюкозой в диагностике отдаленных метастазов дифференцированного рака щитовидной железы У 10-15 % больных с ДРЩЖ встречаются от-даленные метастазы, снижающие общую 10-летнюю выживаемость в этой группе до 40 % [17]. Легкие являются самой частой мишенью отдаленного мета-стазирования, составляя 50 % от всех очагов, ко-сти -25 %, сочетание метастазов в легких и костях встречается в 20 % случаев, метастазы в другие ор-ганы -в 5 % [18].…”
unclassified